Reproductive biology and ecology of Pacific hagfish (Eptatretus stoutii) and black hagfish (Eptatretus deani). Issue 2 (24th April 2021) - Fleury, Aharon G.; MacLennan, Eva M.; Command, Rylan J.; Juanes, Francis
Abstract: The reproductive biology of Pacific hagfish Eptatretus stoutii (Lockington, 1878) and black hagfish Eptatretus deani (Evermann & Goldsborough, 1907) was assessed using current and historical data. Our results found that the reproductive characteristics of both hagfish species reflect those of K ‐selected species, which tend to live long and exhibit slow growth rates, low fecundity (approximately 20 eggs per female) and late maturity. Additionally, females of both species commence maturation prior to males. This study provides a population profile for both species of hagfish, but further assessments are needed to effectively manage a sustainable hagfish fishery.